PENINGKATAN HASIL BELAJAR PPKn MELALUI MODEL PEMBELAJARAN ROLE PLAYING PADA PESERTA DIDIK KELAS IVB SD INPRES TETEBATU KABUPATEN GOWA - Wahyuningsi, Sri; Nursalam; Syahrir, Musdalifah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve students’ learning outcomes in Civic Education (PPKn) through the Role Playing model for fourth-grade students (class IVB) at SD Inpres Tetebatu, Gowa Regency. The research employed Classroom Action Research (CAR) conducted in two cycles, consisting of planning, implementation, observation, and reflection, involving 32 students. The results showed an improvement in learning outcomes, with the average score increasing from 59 in Cycle I to 81 in Cycle II, and learning mastery improving from 38% to 100%. The implementation of learning activities also increased from 92% to 100%. It can be concluded that the Role Playing model is effective in improving students’ learning outcomes, activity, and engagement, and is therefore suitable as an alternative teaching strategy for Civic Education in elementary schools.